2017
DOI: 10.5114/ppn.2017.70545
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sensitivity to rewards, risk-taking, and adaptive behaviour: development of the dual systems perspective

Abstract: Purpose: According to current developmental neuroscience, adolescence is a period of heightened sensitivity to rewards that results in the increased tendency towards risk. This paper presents the current state of knowledge on the consequences of adolescent sensitivity to rewards and indicates directions for future research. The following sections describe how sensitivity to rewards can be directed towards risk-taking, safe or prosocial behaviour, and improved cognitive performance, depending on different task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Hence, adolescents have been shown to be more biased toward reward evaluation by the limbic system compared to the prefrontal system. Previous studies have found that the complete development of the adolescents' prefrontal cortex is near the age of 25 (33,50). Hence, even though the accumbofrontal tract matures early, the prefrontal cortex is one of the last brain regions to reach maturation and is not completely matured until near the age of 25 (33,50).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Hence, adolescents have been shown to be more biased toward reward evaluation by the limbic system compared to the prefrontal system. Previous studies have found that the complete development of the adolescents' prefrontal cortex is near the age of 25 (33,50). Hence, even though the accumbofrontal tract matures early, the prefrontal cortex is one of the last brain regions to reach maturation and is not completely matured until near the age of 25 (33,50).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have found that the complete development of the adolescents' prefrontal cortex is near the age of 25 (33,50). Hence, even though the accumbofrontal tract matures early, the prefrontal cortex is one of the last brain regions to reach maturation and is not completely matured until near the age of 25 (33,50). The prefrontal cortex in general also plays a major role in the regulation of behaviour (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations